Kedudukan Khitan Perempuan Perspektif Hukum Islam - Mubarak, Muhammad Hilal; S, Shuhufi; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Among modern women, there are those who do not agree with the implementation of female circumcision, especially those that damage the reproductive organs, because it is an act of violence against women. This does not mean that there is a contradiction between Islamic teachings and the provisions of “Positive Law” regarding female circumcision, because textually there is no explicit argument that can be referred to do make it mandatory, so that from a fiqh perspective no Ulama of fuqaha requires it. Some Ulama even state that the law on female circumcision in only permissible, it may or may not be carried out, therefore, it is up to parents of the government. If it is considered more beneficial not carry it out, this research is a type of library research, namely research whose object of study uses library data in the form og books, journals, articles and so on as the data source. This research os carried out by reading, reviewing an analyzing various existing literature, in the form of the Qur’an, hadith, MUI fatwa, as well as research argument that requires or considers circumcision for women to be sunnah, either from al-Qur’an, sunnah, ijma’ and qiyas. Qardhawi also revealed that the ulama agrees on this abilities. So there is not a single scholar who says that circumcision is something that is forbidden or that is makruh li tanzih or li tahrim. Therefore, it is nor considered good for someone to criticize the person who did it or consider to have committed an act against the law, uncles it is done excessively to the point that one of the parties feels aggrieved.